2019
DOI: 10.21873/anticanres.13372
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Patients With Malignant Tumors Associated With Mature Cystic Teratomas of the Ovary: A Retrospective Multicenter Italian Study

Abstract: Background/Aim: The aim of the study was to assess the clinical outcome of patients with malignant transformation of an ovarian mature teratoma. Patients and Methods: This study was conducted on 23 patients who underwent primary surgery at three Italian Gynecological Centers. Histologically, nine (39.1%) patients had squamous cell carcinoma, five (21.7%) had a thyroid carcinoma, six (26.1%) had a carcinoid, one (4.3%) patient had papillary renal carcinoma, one (4.3%) had medulloblastoma and one (4.3%) had inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Patients with stage I disease was found to have a significantly better prognosis than stages II, III and IV. 3 , 12 As our patient is 62 years with good performance status, well-differentiated SCC and FIGO stage 1A disease, her survival status can be confirmed upon long-term follow-up only.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Patients with stage I disease was found to have a significantly better prognosis than stages II, III and IV. 3 , 12 As our patient is 62 years with good performance status, well-differentiated SCC and FIGO stage 1A disease, her survival status can be confirmed upon long-term follow-up only.…”
Section: Discussionmentioning
confidence: 65%
“… 4 In a retrospective multicenter Italian study, the other histological variants seen were thyroid carcinoma, carcinoid, papillary renal cell carcinoma, medulloblastoma and intestinal-type mucinous adenocarcinoma. 12 The etiology of SCC transformation in MCTO is unknown. SCC transformation in MCTO may be due to a continuous process of squamous metaplasia, atypical hyperplasia, carcinoma in situ, interstitial infiltration and invasive cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Operation played a pivotal role during both diagnosis and treatment. Patients who received optimal cytoreduction followed with adjuvant chemotherapy seem to have a good outcome with longer survival [8,9]. Optimal cytoreduction can bring a mean survival of 14 months while 7.8 months in suboptimal cases [10].…”
Section: Treatment Of Ovarian Sccmentioning
confidence: 99%
“…Patients who received optimal cytoreduction followed with adjuvant chemotherapy seem to have a good outcome with longer survival. [8,9] Optimal cytoreduction can bring a mean survival of 14 months while 7.8 months in suboptimal cases. [10] Kikkawa et al [6] reported a 79% 5-year-survival rate for patients without residual disease compared with 10.1% for those with residual disease.…”
Section: Treatment Of Ovarian Sccmentioning
confidence: 99%